ANALISIS HUKUM WAKAF ATAS PEMBANGUNAN MASJID DI ATAS HAK GUNA USAHA PTPN IV KEBUN PABATU KABUPATEN SERDANG BEDAGAI - N U R M A U L I N U R M A U L I (PREMISE LAW JURNAL, 2015)
The leasehold which can be used for wakaf is as follows. The leasehold owned by corporation is not peformed by the corporation itself such as the State-owned company, PTPN IV. The company has several estates and one of them is Unit Kebun Pabatu at Pabatu, Serdang Bedagai Disrict. Each afdeling (unit) of PTPN IV, including Unit Kebun Pabatu, has a mosque. The mosque is on the leaseholld of PTPN IV, whereas according to Law No. 41/2004 on Wakaf, its implementing regulation, the Government Regulation No. 42/2006, and Book III of the Presidential Decree No. 1/1991 on the Compilation of the Islamic Law, the mosque in the leasehold of PTPN IV Unit Kebun Pabatu should and can be used as a wakaf object. It means that the land, where the mosque is located, should be taken out from the leasehold of PTPN IV Unit Kebun Pabatu. Keywords: Wakaf on Leasehold Land